DESIGN AND CONSTRUCTION COMPOSTING PLAN AT BPPT JAKARTA OFFICE - Tjahjono., dkk, Hendra (Jurnal Rekayasa Lingkungan)
Waste, both organic and non organic waste generated much cause problems, such as environmental pollution. In large cities waste product per capita ranges between 600- 830 grams per day (Mungkasa, 2004). On the other hand, the city government more difficult to get a processing Waste (landfill). With the launch of Act No. 18 of 2008 on Waste Management in which one important message of the Act is any source of waste should reduce the amount of waste to be disposed to landfill. The results showed that BPPT office waste generation amounted to 0.0108 kg / peg / day or 0002 kg/org/m2/hr paper component composition 59.94% (almost 60%), office space (80.84%), canteen (10.49%), parks (8.67%) and approximately 28.47% of organic material, (Shochib. R,2010). BPPT, as one source of waste from the commercial sector, has reduced the amount of waste that must be disposed of to landfill by utilizing inorganic garbage that still has economic value, while for organic waste, BPPT trying to reduce the amount of waste by processing organic waste into compost, for it will built home composting, which is one place that used to process organic waste into compost. Home composting is designed for a capacity of 1 m3 per week with the long process of 6 weekskeywords: office waste, composting, home composting